2019
DOI: 10.3126/jnbs.v12i1.28184
|View full text |Cite
|
Sign up to set email alerts
|

Online Shopping in Nepal: Preferences and Problems

Abstract: The popularity of online shopping among Nepalese customers has increased with the cost-reduction of technology-based goods, the cost of internet services, and easy access to the internet. At the same time, the convenient modes of payments, and user-friendly, as well as, interactive shopping apps are further paving a pathway to unprecedented growth in the online shopping companies. The online shopping companies in Nepal have been seen following the Business to Consumer (B2C), Customer to Customer (C2C), or the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 8 publications
0
12
0
Order By: Relevance
“…Nepalese online shoppers choose online shopping from a status firm, so firm reputation (β=0.306) is the major influencing factor of online shopping behaviour of boutique products followed by ease of use, trust, and price. Hence, ease of use, trust, firm reputation, product varieties, and price are the main grounds for Internet shopping which is much easier to compare products online (Ahmad, 2018;Rahman et al, 2018;Vaidya, 2019). However, the P-value of price is not significant.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Nepalese online shoppers choose online shopping from a status firm, so firm reputation (β=0.306) is the major influencing factor of online shopping behaviour of boutique products followed by ease of use, trust, and price. Hence, ease of use, trust, firm reputation, product varieties, and price are the main grounds for Internet shopping which is much easier to compare products online (Ahmad, 2018;Rahman et al, 2018;Vaidya, 2019). However, the P-value of price is not significant.…”
Section: Resultsmentioning
confidence: 99%
“…Most designers now communicate with their clients via their websites or social media accounts such as Facebook, Whatsapp, Viber, and Instagram. The rise of online business has also made the market more competitive (Kharel, 2018;Vaidya, 2019). However, there are lots of problems faced by boutiques in Nepal.…”
Section: Research Problemsmentioning
confidence: 99%
See 2 more Smart Citations
“…Each year new e-commerce enters the Nepal market, mostly with websites and app versions in parallel. It was found that the majority of Nepalese customers face issues when using e-commerce (Vaidya, 2019) which is believed to have much more potentials than what it is offering at the moment by using UCD during development of the e-commerce applications. It was found from interviews conducted with Nepalese UX designers that in most cases the design of websites was transformed into its app versions without doing proper research on it.…”
Section: Introductionmentioning
confidence: 99%